Pelatihan Media Pembelajaran Berbasis AI Untuk Guru UPTD SDN 010106 Sei Silau Barat - Latiffani, Chitra; Adi Mas Afandi; Yori Apridonal (STMIK Royal, 2025)
Abstract: This community service describes the implementation of artificial intelligence (AI)-based learning media training for elementary school teachers at the UPTD SDN 010106 Sei Silau Barat, Setia Janji. The background of the activity is the limited understanding and skills of teachers in utilizing AI applications (e.g., ImageFX, Canva AI, and ChatGPT) to create interesting, interactive, and student-specific learning media. The implementation method includes three stages: preparation (interviews & needs observations), implementation (face-to-face workshops, demonstrations, and supervised independent practice), and evaluation (pre-post surveys and work assessments). This can be seen from the results of the pre-test and post-test conducted at the beginning and end of the training, from 31% pre-test to 88% post-test showing a significant difference. The results of this training showed a 57% increase in teachers' practical understanding, the development of AI-based teaching media in core subjects, and plans for sustainable adoption in the classroom. This activity contributes to improving educators' ICT competencies and encouraging the integration of modern technology in elementary schools. Keywords: artificial intelligence; community service; elementary school teachers; imageFX; learning media; training. Abstrak: Pengabdian ini mendeskripsikan pelaksanaan pelatihan media pembelajaran berbasis kecerdasan buatan (AI) bagi guru sekolah dasar di UPTD SDN 010106 Sei Silau Barat, Setia Janji. Latar belakang kegiatan adalah masih terbatasnya pemahaman dan keterampilan guru dalam memanfaatkan aplikasi AI (misalnya ImageFX, Canva AI, dan ChatGPT) untuk membuat media ajar yang menarik, interaktif, dan sesuai karakteristik siswa. Metode pelaksanaan meliputi tiga tahap: persiapan (wawancara & observasi kebutuhan), pelaksanaan (workshop tatap muka, demo, dan praktik mandiri tersupervisi), serta evaluasi (pre–post survey dan penilaian karya). Hal ini dapat diliat dari hasil pre-test dan post-test yang dilakukan di awal dan di akhir pelatihan, dari 31% pre-test ke angka 88% post-test menunjukan perbedaan yang signifikan. Hasil pelatihan ini menunjukkan peningkatan sebesar 57% pada pemahaman praktis guru, penyusunan media ajar berbasis AI pada mata pelajaran inti, serta rencana adopsi berkelanjutan di kelas. Kegiatan ini berkontribusi pada peningkatan kompetensi TIK pendidik dan mendorong integrasi teknologi modern di sekolah dasar. Kata kunci: guru SD; imageFX; kecerdasan buatan; media pembelajaran; pelatihan; pengabdian masyarakat.